We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
332
1
avatar+4684 

Help.

 Dec 21, 2017
 #1
avatar+99237 
+1

2.5x - 3y  = -13     (1)

3.25x - y  =  -14  ⇒    y  =  3.25x + 14     (2)

 

Sub (2) into (1)  and we have

 

2.5x - 3 [ 3.25x + 14]   = -13     simplify

 

2.5x - 9.75x - 42  =  -13    

 

-7.25x  - 42  = -13       add 2 to both sides

 

-7.25x =  29               divide both sides by -7.25

 

x  =  -4

 

And using  (2), y  =  3.25(-4)  + 14   =  -13  + 14  = 1

 

So  {x, y}   =  { -4, 1 }

 

 

cool cool cool

 Dec 21, 2017

16 Online Users

avatar
avatar
avatar